2021
DOI: 10.1038/s41598-021-03724-8
|View full text |Cite|
|
Sign up to set email alerts
|

Polarization-sensitive optical coherence tomography monitoring of percutaneous radiofrequency ablation in left atrium of living swine

Abstract: Radiofrequency ablation (RFA) is commonly used to treat atrial fibrillation (AF). However, the outcome is often compromised due to the lack of direct real-time feedback to assess lesion transmurality. In this work, we evaluated the ability of polarization-sensitive optical coherence tomography (PSOCT) to measure cardiac wall thickness and assess RF lesion transmurality during left atrium (LA) RFA procedures. Quantitative transmural lesion criteria using PSOCT images were determined ex vivo using an integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…We have already shown that PSOCT at the tip of an ablation catheter can provide more information and feedback for determining lesion transmurality [12][13][14] . We have designed and built a cardiac ablation catheter with PSOCT.…”
Section: Innovation and Impact Of Polarization Sensitive Optical Cohe...mentioning
confidence: 99%
“…We have already shown that PSOCT at the tip of an ablation catheter can provide more information and feedback for determining lesion transmurality [12][13][14] . We have designed and built a cardiac ablation catheter with PSOCT.…”
Section: Innovation and Impact Of Polarization Sensitive Optical Cohe...mentioning
confidence: 99%
“…PS-OCT reveals tissue birefringence features that are invisible to structural (non-PS) OCT imaging. PS-OCT has been used to image skeletal muscle, 17 heart, 18 , 19 and brain. 20 In all of these procedures, PS-OCT was added to a scanned-beam approach.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have adopted optical methods to directly visualize lesion delivery and to predict lesion dimensions [14][15][16]. Catheter based optical coherence tomography (OCT) allows immediate imaging feedback to monitor RF lesion formation [14,[17][18][19][20][21][22]. In photoacoustic imaging, real-time assessment of RF ablation lesion formation in the left atrium was demonstrated with clinically translatable instruments [23].…”
Section: Introductionmentioning
confidence: 99%